2015
DOI: 10.1038/cgt.2015.7
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration of dendritic cells and T lymphocytes predicts favorable outcome in epithelial ovarian cancer

Abstract: We aimed to analyze the association between the distribution of dendritic cells (DC) with expression of tumor-infiltrating T lymphocytes and clinicopathologic parameters with prognosis in epithelial ovarian cancer (EOC). Thirty-three EOC patient samples were surgically resected, and pathology was examined for clinicopathological variables. Expression of S-100, CD1a, CD45RA and CD45RO was detected using the avidin-biotin complex immunohistochemical technique. The correlation of protein expression with surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 12 publications
3
26
0
Order By: Relevance
“…9 Histopathological analysis of a variety of human tumors showed high concentrations of T lymphocytes is associated with better prognosis in melanoma, breast cancer, prostate cancer, non-Hodgkin lymphoma, head and neck cancer, NSCLC, esophageal cancer and urethral carcinoma. 10, 11, 12 In an earlier study of NSCLC, a large number of tumor infiltrating CD8+ T cells were found to induce tumor cell apoptosis. 13 CD4+ T and B lymphocytes are a double-edged sword in tumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…9 Histopathological analysis of a variety of human tumors showed high concentrations of T lymphocytes is associated with better prognosis in melanoma, breast cancer, prostate cancer, non-Hodgkin lymphoma, head and neck cancer, NSCLC, esophageal cancer and urethral carcinoma. 10, 11, 12 In an earlier study of NSCLC, a large number of tumor infiltrating CD8+ T cells were found to induce tumor cell apoptosis. 13 CD4+ T and B lymphocytes are a double-edged sword in tumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the correlation between increased CD8 + T-cell infiltration and good clinical outcome was recently described in the previous unstudied neoplasias, including GIST (Rusakiewicz et al, 2013), oropharyngeal ( Jung et al, 2013;NĂ€sman et al, 2012;Wansom et al, 2012), thyroid (Cunha et al, 2012), and biliary tract cancer (Goeppert et al, 2013). Poor (Salvesen & Akslen, 1999) Good Poor (Lan et al, 2013) Good (Eisenthal et al, 2001;Zhang et al, 2015) Good Sato et al, 2005;Zhang et al, 2003) Oesophageal cancer -Poor (Guo et al, 2007) Poor (Shigeoka et al, 2013) Good (Furihata et al, 1992;Ishigami et al, 2003aIshigami et al, , 2003bLu et al, 2013) Good (Hsia et al, 2005) Colorectal cancer Good (Bindea et al, 2013;Menon et al, 2004) Poor (BarberaGuillem et al,…”
Section: Role Of T Cellsmentioning
confidence: 90%
“…Their link with clinical prognosis has been reported in a variety of human solid tumors. The majority of these studies report that an extensive infiltration with DC is associated with increased OS and cover many tumors types, including melanoma (Gerber et al, 2014;LadĂĄnyi et al, 2007;Neagu et al, 2013;Simonetti et al, 2007), HCC (Cai et al, 2006;Yin et al, 2003), gallbladder (Furihata et al, 2005;Nakakubo et al, 2003), oral (Reichert et al, 2001), esophageal (Furihata et al, 1992;Ishigami et al, 2003a;Lu et al, 2013), gastric (Amoueian et al, 2015Ananiev et al, 2011;Kashimura et al, 2012;Tsukayama et al, 2005), NSCLC (Al-Shibli et al, 2009;Dai et al, 2010;Hald et al, 2013;Inoshima et al, 2002;Johnson et al, 2000), colorectal (Gulubova et al, 2012;McMullen et al, 2010;Nakayama et al, 2003;VĂ€yrynen et al, 2014), bladder (Inoue et al, 1993), breast (Iwamoto et al, 2003;La Rocca et al, 2008;Lespagnard et al, 1999;Park et al, 2012), endometrial (Honig et al, 2005;Lijun et al, 2012), and ovarian cancer (Eisenthal et al, 2001;Zhang et al, 2015). Nevertheless, the infiltration with CD123 + plasmacytoid DC has been associated with shorter OS in breast cancer ( Jensen et al, 2012;Treilleux et al, 2004), as well as the presence of CD208 + and CD1a + DCs in colorectal (Sandel et al, 2005)...…”
Section: Role Of Dcsmentioning
confidence: 95%
“…It is possible that this is a direct consequence of the cancer-mediated altered myelopoiesis but it could also be the outcome of a PGE2-driven redirected differentiation of DC to mMDSC. 36 DC are an important component of the EOC microenvironment of patients with better survival, 37 hence therapeutic approaches to normalize their levels are warranted. Potentially, targeting PGE2 may be of help.…”
Section: Discussionmentioning
confidence: 99%